Job insecurity during the COVID-19 pandemic and counterproductive work behavior: The sequential mediation effects of job stress and organizational identification and the buffering role of corporate social responsibility - Kim, Byung-Jik; Lee, Julak; Jung, Jeyong; Kim, Min-Jik (Frontiers in Public Health, 2023)
Swift social and economic environmental changes such as those associated with the COVID-19 pandemic have led to decreased job security. Although numerous previous studies have examined the influence of job insecurity on employee perceptions, attitudes, and behaviors, the link between job insecurity and negative behavior and its underlying or intermediating mechanisms remain underexplored. The significance of an organization's positive behaviors, which fall under the umbrella of corporate social responsibility (CSR), also deserves more attention. To address these gaps, we examined both the mediator and the moderator in the association between job insecurity and negative employee behavior by establishing a moderated sequential mediation model. We hypothesized that the levels of employee job stress and organizational identification sequentially mediate the relationship between job insecurity and counterproductive work behavior as a representative negative behavior. We also hypothesized that CSR activities play a buffering role that moderates the influence of job insecurity on job stress. We used three-wave time-lagged data collected from 348 employees in South Korean organizations to demonstrate that job stress and organizational identification sequentially mediate the relationship between job insecurity and counterproductive work behavior, and that CSR activities function as a buffering factor that decreases the influence of job insecurity on job stress. The results of this research suggest that the levels of job stress and organizational identification (as sequential mediators) as well as CSR activities (as a moderator) are underlying mechanisms in the link between job insecurity and counterproductive work behavior.